2016
DOI: 10.1055/s-0042-103028
|View full text |Cite
|
Sign up to set email alerts
|

Therapieformen der Dritten Welle der Verhaltenstherapie bei Zwangsstörungen: Sinnvolle Ergänzung zu KVT? Aktueller Wissensstand

Abstract: Cognitive behavioral therapy (CBT) with exposure is the state of the art and most efficient treatment for obsessive compulsive disorder and recommended as treatment of 1st choice according to guidelines. Therapies of the third wave, such as mindfulness based approaches (ACT, MBCT), metacognitive therapy, CBASP or schema therapy, have become more popular over past few years. A small number of studies that investigated some of these therapies show promising results. However, due to the small number of available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Future research is warranted to establish the same. [91] There is increasing integration of mindfulness and acceptance strategies along with traditional/conventional CT/CBT in clinical practice. However, the manner of integration is based on several factors including the clinician's judgment.…”
Section: Discussionmentioning
confidence: 99%
“…Future research is warranted to establish the same. [91] There is increasing integration of mindfulness and acceptance strategies along with traditional/conventional CT/CBT in clinical practice. However, the manner of integration is based on several factors including the clinician's judgment.…”
Section: Discussionmentioning
confidence: 99%
“…B. die Cognitive Remediation Therapy (CRT) [13], Essbegleitung [14] oder die Schematherapie [3] erweitert. Letzteres gehört zu den sogenannten Therapieformen der Dritten Welle der Verhaltenstherapie [15] und wird bereits zur zeitgleichen Behandlung von Komorbiditäten bei Abhängigkeitserkrankungen und Borderline-Persönlichkeitsstörung eingesetzt [16]. Ebenfalls finden sogenannte E-Mental Health-Methoden [17] und Kurzinterventionen [18] Verwendung in der Behandlung von Essstörungen.…”
Section: Komorbiditäten In Der Behandlung Von Essstörungen Und Adiposunclassified
“…A new study reported the beneficial effects of MBCT in OCD, depression and anxiety symptoms as well as obsessive beliefs through improving mindfulness skills and self-compassion in the experimental group vs. controls (18). In addition, other third wave treatment approaches such as Acceptance and Commitment Therapy (ACT) and Mindfulness Based Stress Reduction are also reported as beneficial in relapsed OCD symptoms (14,(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%